Evaluating catalytic and antibacterial properties of composite hydrogel based on biomimetically synthesized CeO2 nanoparticles anchored onto microcrystalline cellulose/reduced graphene oxide - Saima, Sohni; Abdullah, -; Esraa M., Bakhsh; Faryal, Mazhar; Waqas, Ahmad; Junidah, Lamaming; Arshad, Iqbal; Hafiz, Nidaullah; Murtaza, Sayed; Sher Bahadar, Khan (Elsevier B.V., 2025)
The present study suggests a scalable approach to fabricate a composite hydrogel based on cerium dioxide (CeO2) nanoparticles anchored onto microcrystalline cellulose (MCC) in a three-dimensional reduced graphene oxide (rGO) hydrogel with bifunctional performances in water reclamation. Herein, CeO2 nanoparticles were biosynthesized using Banana pseudo-stem extract as a stabilizer and reducing agent. Afterwards, a series of hierarchical scaffolds of 3D hydrogels were fabricated employing different contents of CeO2, MCC and rGO via. selfassembly process. Analytical techniques provided useful insights regarding chemical structure and morphology of the fabricated hydrogel. Results showed that the proportion of CeO2, MCC and rGO controlled performance characteristics of the resulting composite hydrogels. Under optimal conditions, 95 % of the catalytic reduction of methylene blue dye solution (50 ppm) was achieved rapidly in the presence of catalyst (20 mg) using NaBH4 solution (0.25 M) at ambient temperature. Recyclability tests demonstrated long term stability of composite hydrogel all through four successive cycles without any significant loss of its effectiveness. Moreover, asprepared hydrogels demonstrated appreciable antibacterial potential against Gram-positive and Gram-negative bacteria. It is evident that using MCC and rGO as supporting substrates with CeO2 accorded more functions to the resulting composite hydrogel due to synergistic effects that resulted in a high performance, easily retrieving and steady material for wastewater purification.